Gilles Deleuze: un pensamiento sin imagen - Garzón Gualteros, Marcela (Universidad Antonio Nariño, 2021)
Gilles Deleuze, author whose propositions we are about to study in this paper —especially the ones presented in the work Difference and Repetition (2002)—, frees thought of the predominance of identity, of the image of classic thought that lies on the necessary condition of Sameness. With this inexpedient thinker we will see the display of a thought without image —a thought that thinks about itself—, free of postulates and presuppositions, free of all sorts of identity, of all immovability, of all continuous permanence.